ANALISIS LAPORAN KEUANGAN DALAM RANGKA MENILAI KINERJA PERUSAHAAN PT. TELEKOMUNIKASI INDONESIA TBK. (PERIODE 2014-2018) - Tri Puji Astuti; Mohammad Taufiq (Universitas Nahdlatul Ulama Sidoarjo, 2020)
This research is a qualitative research with descriptive approach. Data collection techniques in this study are documentation techniques with secondary data, namely financial statement from 2014 to 2018 which include balance sheet and income statements and annual reports from 2014 to 2018. Ratio analsis techniques which include Liquidity ratio, Solvability, Activity, and Profitability. While the method used is time series analysis. After the analysis is carried out, it can be seen that the company’s financial performance is carried out from a good level of Liquidity in meeting its short term obligations, because the Current Ratio and Cash Ratio are able to pay current debts and operating costs. The value of the Solvability ratio, namely the Debt Ratio and Debt to Equity Ratio, were below the average service industry. This shows the decrease in company operations that are financed by loan funds. The value of the Activity ratio, namely Total Asset Turnover and Fixed Asset Turnover, which turnover is very slow, and the ratio is below the average of the service industry. The value of the Profitabilityratio, namely Gross Profit Margin and Net Profit Margin, is in poor condition, because the value is below the service industry average, but in good condition based on the Rate On Equity. And the condition of company’s performance from a financial perspective is said good, and based on the customer perspective it is said to be good.